2021
DOI: 10.34312/jjec.v3i2.11194
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Hasil Belajar Kimia Dasar Mahasiswa STKIP PI Makassar Melalui Penerapan Model Pembelajaran Kimia Berbasis Concept Mapping Dipadu Teams Games Tournament

Abstract: Penelitian ini merupakan Penelitian Tindakan Kelas (Classroom Action Research) yang bertujuan menerapkan model pembelajaran kimia Berbasis Concept Mapping Dipadu Teams Games Tournament untuk meningkatkan hasil belajar kimia dasar mahasiswa STKIP PI Makassar. Adapun subjek penelitian adalah mahasiswa kelas I A, berjumlah 35 mahasiswa. Pelaksanaan ini dilaksanakan dua siklus, dimana setiap siklusnya terdiri dari tiga kali pertemuan dan satu pertemuan evaluasi. Dari hasil kegiatan pembelajaran yang telah dilakuka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…The learning program developed, namely RPS and RTM, both fulfilled the requirement of KKNI. Munandar and Rumape (2021) used concept mapping learning model integrated with team group tournament type of cooperative learning. The results revealed that the average students' achievement increased from 54,14 to 75,43 and the mastering learning of student increased from 47,14% to 88,57%.…”
Section: Introductionmentioning
confidence: 99%
“…The learning program developed, namely RPS and RTM, both fulfilled the requirement of KKNI. Munandar and Rumape (2021) used concept mapping learning model integrated with team group tournament type of cooperative learning. The results revealed that the average students' achievement increased from 54,14 to 75,43 and the mastering learning of student increased from 47,14% to 88,57%.…”
Section: Introductionmentioning
confidence: 99%